Energetic budget of diploid and triploid eastern oysters during a summer die-off - Bodenstein, Sarah; Casas, Sandra M.; Tiersch, Terrence R.; La Peyre, Jerome F. (Frontiers in Marine Science, 2023)
Triploid oysters are widely used in off-bottom aquaculture of eastern oysters, Crassostrea virginica. However, farmers of the Gulf of Mexico (GoM) and Atlantic coast estuaries have observed unresolved, late-spring die-offs of triploid oysters, threatening the sustainability of triploid aquaculture. To investigate this, the physiological processes underlying oyster growth (e.g., feeding, respiration) and mortality of one-year-old diploid and triploid oysters were compared in early summer following an uptick in mortality. It was predicted that higher triploid mortality was the result of energetic imbalances (increased metabolic demands and decreased feeding behavior). Oyster clearance rates, percentage of time valves were open, absorption efficiency, oxygen consumption rates (basal and routine), ammonia excretion rate were measured in the laboratory and scope for growth was calculated. In addition, their condition index, gametogenic stage, Perkinsus marinus infection level, and mortality were measured. Mortality of triploids in the laboratory was greater than for diploids, mirroring mortality observed in a related field study. The physiological parameters measured, however, could not explain triploid mortality. Scope for growth, condition index, and clearance rates of triploids were greater than for diploids, suggesting sufficient energy reserves, while all other measurements where similar between the ploidies. It remains to be determined whether mortality could be caused from disruption of energy homeostasis at the cellular level.